PEMBINAAN ENTREPRENEURSHIP ATLET KONI JATIM DALAM PROGRAM “UC SPORTPRENEUR” - Christina Whidya Utami; Metta Padmalia; Christina Sudyasjayanti; Yosef Evandro Ernantyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
The success of Indonesian athletes at the 2018 ASIAN Games shows the size of the potential of Indonesian youth in various sports. The young generation as the foundation of the nation's hope, a big responsibility for the development of the Indonesian nation to the young Indonesians are able to compete and be dynamic in this 4.0 era, so they must have thoughts that can increase competitiveness, such as persistence, strong leadership, desire to continue to excel (need of achievement), responsive to various changes that will occur (calculated risk taking). Ciputra University through the UC Sportpreneur Academy coaching program has succeeded in providing answers to these challenges by providing training to outstanding athletes from KONI East Java. UC Sportpreneur Academy as a form of collaboration between KONI East Java and the Faculty of Management and Business, University of Ciputra, is a form of activity that will depart from the results of athletes in Indonesia. The aim of the program is to improve the entrepreneurial competence of outstanding athletes who are nearing retirement and develop business ideas from them as a source of income in the future when they finally retire from the world of sports. The UC Sportpreneur Academy activity is a good and beneficial activity for both parties, both Ciputra University and KONI of East Java Province. However, there are still many things that need to be improved from this activity, for example the entrepreneurial atmosphere that can still be improved.ABSTRAK:Keberhasilan atlet Indonesia di ajang ASIAN Games 2018 menunjukkan betapa besarnya potensi kaum muda Indonesia di berbagai bidang olahraga. Generasi muda sebagai tumpuan harapan bangsa, memikul tanggung jawab besar akan pengembangan bangsa Indonesia ke depannya. Kaum muda Indonesia dituntut mampu bersaing dan berdinamika di era 4.0 ini, sehingga mereka harus memiliki pemikiran yang dapat meningkatkan daya saing, seperti pantang menyerah (persistence), leadership kuat, keinginan terus berprestasi (need of achievement), cepat tanggap terhadap berbagai perubahan yang akan terjadi (calculated risk taking). Universitas Ciputra melalui program pembinaan bertajuk UC Sportpreneur Academy telah berhasil memberikan jawaban atas tantangan tersebut dengan memberikan pelatihan pada para atlet berprestasi dari KONI Jatim. UC Sportpreneur Academy sebagai bentuk kerja sama antara KONI Provinsi Jawa Timur dengan Fakultas Manajemen dan Bisnis Universitas Ciputra, merupakan bentuk kegiatan yang berangkat dari keprihatinan akan keberlanjutan atlet di Indonesia. Tujuan program tersebut adalah untuk meningkatkan kompetensi berwirausaha atlet berprestasi yang mendekati masa pensiun dan mengembangkan ide bisnis dari mereka sebagai sumber penghasilan di kemudian hari ketika mereka akhirnya pensiun dari dunia olahraga. Kegiatan UC Sportpreneur Academy merupakan kegiatan yang baik dan bermanfaat bagi keduabelah pihak, baik Universitas Ciputra maupun KONI Provinsi Jawa Timur. Akan tetapi masih banyak hal yang perlu diperbaiki dari kegiatan ini, misalnya atmosfer entrepreneurship yang masih bisa ditingkatkan lagi.